Clinical effectiveness of a highly standardized and bioavailablemixture of flavonoids and triterpenes in the management of acutehemorroidal crisis - Di Pierro, F.; Spinelli, G.; Monsù et al., G. (Acta Biomedica Atenei Parmensis, 2011)
Background and aim of the work: Patients with acute haemorrhoidal crisis often need of an immediate and effective pharmacological approach to alleviate their pain, bleeding and swelling or have to be referred by the general practitioner to the surgeon for a definitive treatment. Effective and not invasive treatment control of the acute crisis could be of practical use in order to avoid or to delay invasive procedures to a time more convenient for the patient and/or for the surgeon. Methods: After enrolling, according to the group treatment, every patient starts taking 1 tablet every 8 hours for 7 days of Emospid® or 2 tablets every 8 hours for 7 days of MMDH tablets. According to a simplified PATE 2000 classification, the following parameters were evaluated: haemorrhoidal grade, internal and external haemorrhoids, internal and external oedema, internal and external thrombosis, bleeding, bleeding intensity, pain, itching, defecation problems and urgency, tenesm, mucus in stools and sphinterial tone. Results: In the Emospid® group, within the considered period, 35 patients out 40 shift downwards of 1 grade of the haemorrhoidal scale (from III to II and from II to I); 22 out of 29 stop bleeding; bleeding intensity drops by about 90%; pain ceased in 33 out of 38; pain intensity drops by about 75%; itching ceased in 25 out 35; tenesm ceased in 32 out of 33; sphinterial tone reduced from hypertonic to normal in 19 out 24; mucus in the stools was found in 3 out of 12; 12 out 35 still presented defecation disorders; defecation urgency was found in 2 out of 14; need to defecate in 2 times was found in 1 out of 17; acute events (external and/or internal oedema, external and/or internal thrombosis) was found in 10 out of 36. In the MDHH group results were, in terms of global evaluation, inferior of about 25-50% according to the considered parameter when compared with the one got by the Emospid® treatment. Conclusions: Patients with acute haemorrhoidal crisis may be successfully treated with Emospid® in order to avoid or to delay, if acute crisis relapsed, invasive procedures. Moreover, the treatment with Emospid® shows to be more effective, if compared with MMDH, in counteracting acute haemorrhoidal crisis.